Place and Memory. In the Search for Premises of Biographical Research - Czajkowska, Agata (INSTED: Interdisciplinary Studies in Education & Society, 2016)
This paper presents an attempt of reflection on the categories of ?place? and ?memory? and their inherence in biographical research. The starting point of this discussion is the P. Connerton?s work entitled How Modernity Forgets (Connerton 2009) and the concept of ?places of memory? by P. Nora (Nora 2009). Recognition of the above categories will be preceded by the look at the meaning of the place as the memory medium. Other terms that are essential for the understanding of this subject, such as memory space, spatial turn and place memory, will be referred to.